Potential Assessment and Ecotourism Carrying Capacity in Suwi Wetlands on Essential Ecological Areas East Kutai, Indonesia - Sulistyorini, Iin Sumbada; Edwin, Muli; Kadang Allo, Jerlita; Kusneti, Monica; Isa, Nur Linda (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2025)
The conservation and protected areas within the Essential Ecological Areas of the Mesangat-Suwi Wetlands are ecologically significant due to their high biodiversity, local community fishing resources, and habitat for endangered species. The distinctiveness of the Suwi Wetlands as a habitat for proboscis monkeys (Nasalis larvatus) and Crocodylus siamensis enhances the prospects for sustainable ecotourism through natural attractions. This study references the evaluation of natural tourism attractions' potential and the carrying capacity of both biotic and abiotic environments. Of the fourteen prospective variables evaluated, nine exhibit significant potential: natural attractions, market potential, surrounding circumstances, climate, accommodation, supporting infrastructure, security, area carrying capacity, and market share. The Physical Carrying Capacity (PCC) for the maximum number of visitors is 80 individuals per day, whereas the Real Carrying Capacity (RCC) is 3 individuals per day. The quantity of visitors is consistent with the condition of biophysical characteristics. Wetlands of significant conservation significance must be safeguarded via sustainable ecotourism approaches. Conservation initiatives beyond forested regions should focus on cultivating ecotourism potential to guarantee long-term environmental sustainability.